1989
DOI: 10.1007/bf00218804
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of hypocalcin in the endocrine cells of the corpuscles of Stannius in three teleost species (trout, flounder and goldfish)

Abstract: Summary. In order to identify the cell-type responsible for the production of hypocalcin (the recently isolated hypocalcemic hormone of teleost Fish), the corpuscles of Stannius (CS) of trout, flounder and goldfish, were immunocytochemically stained with antisera raised against trout hypo calcin. The secretory granules of the type-1 cells of the CS, considered to be the hypocalcin-producing cells, showed intense immunoreactivity in all species examined. However, in trout and flounder, the secretory granules pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…5 It has been demonstrated that CS extracts inhibit Ca 2ϩ uptake by three salmonids and the American eel (380), and stanniectomy of the eel was associated with increased plasma Ca 2ϩ levels, which were corrected when STC was injected (280), so STC is generally considered to be the major hypocalcemic factor in fishes (767). The cellular site of STC production in the CS has been localized by immunocytochemistry (798), and hypercalcemia in the rainbow trout is associated with increased release of immunoreactive STC from the CS (219). Moreover, intraperitoneal injection of CaCl 2 into the rainbow trout and European eel stimulated STC release from the CS (279), as did acclimation of the eel to seawater versus fresh water (278).…”
Section: Stanniocalcinmentioning
confidence: 99%
“…5 It has been demonstrated that CS extracts inhibit Ca 2ϩ uptake by three salmonids and the American eel (380), and stanniectomy of the eel was associated with increased plasma Ca 2ϩ levels, which were corrected when STC was injected (280), so STC is generally considered to be the major hypocalcemic factor in fishes (767). The cellular site of STC production in the CS has been localized by immunocytochemistry (798), and hypercalcemia in the rainbow trout is associated with increased release of immunoreactive STC from the CS (219). Moreover, intraperitoneal injection of CaCl 2 into the rainbow trout and European eel stimulated STC release from the CS (279), as did acclimation of the eel to seawater versus fresh water (278).…”
Section: Stanniocalcinmentioning
confidence: 99%
“…1988: Wagner et al 1988 and the trout (Kaneko el al. 1988;Wendelaar Bonga et al 1989) STC antisera have been characterized previously.…”
Section: Primary Antiseramentioning
confidence: 99%
“…Polyclonal rabbit anti-STC1 antibodies were a gift from Dr. Gert Flik (Radboud University, Nijmegen, Netherlands). 35 Antibodies for mouse pan-macrophage marker (CD68) were purchased from AbD Serotec (Raleigh, NC). Actin antibodies were purchased from Chemicon (Temecula, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Five-m sections were cut, dried, and rehydrated. Labeling was performed using polyclonal rabbit anti-STC1 (1:1000 dilution) 35 or monoclonal rat anti-mouse F4/80 antigen antibodies (1:100 dilution), and detection was performed using peroxidase enzyme-based detection system (Vector Laboratories, Burlingame, CA). Control for labeling was performed in the presence of nonimmune IgG, and showed no staining.…”
Section: Immunohistochemistrymentioning
confidence: 99%